Regional innovation networks evolution and firm performance: one or two way causality? - Joana Almodovar; Aurora Amélia Castro Teixeira (European Regional Science Association (ERSA), 2004)
Current research has revealed the existence of a relationship between networks and firm growth (Jarillo, 1989; Huggins, 2000). Nevertheless, network content and specificity and how these networks influence firm economic and financial performance has been little investigated. In addition, the influence of regions in relation to the spatial proximity on inter-firm networks should be an additional dimension taken into account if the determinants of firm performance are to be adequately understood. The most important linkages tend to be characterised by territorial closeness and have relevant effects over firm performance (Oerlemans and Meeus, 2002; Lechner and Dowling, 2003). Since automobile industry can be regarded as a worldwide cluster, where the evolution tendency on constructor's behalf has been to gradually delegate technological competencies into industry suppliers, the regional networks acquire a renewed importance beyond the recognized benefits of sharing, interaction and reciprocity. Given that networks “do not happen in a virtual space where spatial proximity does not matter” (Lechner and Dowling, 2003: 9), the Portuguese inter-firm cooperation within the automotive industry can be regarded as a possible source of regional advantage for responding to globalisation competitive challenges. Thus, in this paper we explore how firms grow through the use of external linkages and become competitive, using case study material based on a Portuguese inter-firm network of the auto-parts industry (ACECIA) and one of its founding members, Simoldes. Using a set of performance indicators, we concluded that its positive evolution was contemporaneous and last beyond ACECIA's constitution date. Moreover, evidence of possible leverage effects from the combined collaboration emerged indicating that the relation between networks and firm performance implies a two-way causality association.
Keywords: 330